The Influence Of Marketing Mix To The Inpatient Loyalty At The General District Majenang Hospita - Indra Setya Permana; Susanto Susanto (Jurnal Admmirasi, 2015)
Background: Hospital as the provider of health service must have competitive advantage. Consumers more clever and educated that make increase the wish and hope of health service quality. The implementation of the right marketing strategies have important role to realize inpatient loyalty against hospital service quality. Purpose: To know the influence of marketing mix to the inpatient loyalty at the general district Majenang hospital. Method: This research is inferential analytic with cross sectional approach. The populations of this study are in patients who utilize the hospitalization at the RSUD Majenang. The sampling technique use purposive sampling with amount of samples as 100 peoples. The data collecting use questionnaire. The data analysis using multiple regressions. Result: statistical analyze used multiple regressions prove that price, process, personnel and physical in partial and stimulants way influence the inpatient loyalty at the general district Majenang hospital (p<0,05). Conclusion: Price, process, personnel and physical influence the inpatient loyalty at the general district Majenang hospital.